Analisis Skema Mencetak Gol Timnas Senior Indonesia Di Piala AFF Tahun 2020 - Muhammad Zufar Fikri Nurhasan; Mokhamad Nur Bawono; Joesoef Roepajadi; Soni Sulistyarto (Jurusan Pendidikan Kesehatan dan Rekreasi, 2023)
Background: Nowadays, football is not only played for recreational purposes and to fill spare time, but become a sport that competed in the achievement events. Football is a team game played by eleven players each including a goalkeeper whose aim is to get the ball into the opponent's goal and maintain his own goal defense. Because each goal has its own tactics and schemes, this study aims to analyze the scheme of scoring goals and the opportunities for goals to occur through the process (heading, shooting, and cheating) of the senior Indonesian national team in the 2020 AFF Cup. Methods: This study uses descriptive method with a quantitative approach. Results: And the result is that the goal analysis for scheme one cooperates with 2 players, namely players A and B, then the process of achieving goals through the middle or the position of the opponent's penalty box and the occurrence of goals is created by players in position B. Scheme two cooperates with 5 players, namely player A , B, C, D, and E, the goal occurred through the middle of the opponent's penalty box and was created from a player in position A. Scheme three cooperated with 3 players, namely players A, B, and C, the goal occurred 12 meters on the left side of the attack or on the left side of the opponent's defense, and the goal is scored from a player in position C. Conclusions: There are three attack schemes that can score goals in the 2020 AFF Cup, namely two-member cooperation, five-member cooperation and three-member cooperation.